Ludovico Silva and the Move to Critical Stances in Latin American Communication Studies - Calles-Santillana, Jorge Alberto (Javnost-The Public, 2006)
Despite his intellectual impact in the field of communication studies during the 1970s, Ludovico Silva is hardly remembered today even in his native country, Venezuela. Showing a singular intellectual honesty, Ludovico Silva worked on a general theory of ideology, challenging the official Marxism and leftist political forces of the age. Based on Marx´s difference between use value and exchange value, Silva argued that the Marxist category of surplus needed an equivalent in the symbolic realm; hence he developed the concept of ideological surplus in order to reject mechanical interpretations of ideology. Thus, Silva, among other scholars, contributed to Latin American communication studies by incorporating power and domination as structural forces in the making of social relations. The ideological power of media became the ultimate concern in media studies, questioning the explanatory value of the functionalist and quantitative studies focused on media effects, which were dominant at that time. Silva´s work is recovered here in a historical perspective, stressing his intellectual commitment to the truth, and his contribution to move Latin American communication studies from a conventional academic stance to a critical one.